Essential oil analysis and Antibacterial activities of some medicinal plants - Amrollahi Hadi; Mohammadi Abolfazl; Dehpour Ahmadreza; Nazari Hossein (International Journal of Phytomedicine, 2012)
The extraction of medicinal plants has been used traditionally against pathogenic bacteria that caused infectious disease in human and Microbial spoilage of food and have been used safely in herbal medicine as antimicrobial compounds. In the prese nt study, The antibacterial activities of the oils were evaluated against human and animals pathogenic bacteria; the three gram positive bacteria; Staphylococcus aureus, Listeria monocytogenes, Streptococcus pneumonia and four gram negative bacteria; Pseudomonas aeruginosa, Klebsiella pneumoni, Escherichia coli and Salmonella typhi. In this assay, the selective plants were reported ethnobotanical uses traditionally and also referenced in some herbal medicine text. The essential oil of Stachys pubescens, Coriandrum sativum and Cinnamomum zelanicum, Bupleurum falcatum were prepared by hydrodistillation. The oils were analyzed by GC/MS. The number of 6, 10, 15 and 23 components was identified in C. sativum, C. zelanicum, B. falcatum and S. pubescens respectively. The MIC and MBC of oils determined with broth microdilution and agar diffusion method on bacterial strains. Results from the antibacterial testing indicated that B. falcatum, S. pubescens and C. zelanicum essential oils showed high activities and inhibited the growth all of the selected bacteria. While the essential oil of C. sativum displayed the moderate potential activity. Our finding supported the notion that plant essential oils composition or total extract may have a role as pharmaceuticals and preservatives effects as safely and effective drugs with low resistance against microorganisms. Therefore, these essential oils could be used for management of these pathogens as a potential source of sustainable eco-friendly botanical bactericides.